Association of Polycystic Ovaries in Primary Infertile Women with Ovarian and Uterine Morphology - Ambreen Usmani , Muhammad Saeed ,Rehana Rehman , Zia ul Islam; Fehmida Shaheen, Attiya Begum (Journal of Rawalpindi Medical College, 2014)
Background: To measure the effect of age on ovarian and uterine morphology in infertile women with polycystic ovaries (PCO) Methods: In this observational cross sectional study 100 primary infertile women with PCOs (confirmed by ultrasonography) were subdivided into two age groups. Group-I included between age groups 20-30 years and Group II ranged from 31- 40 years. The ovarian volume (OV), follicles count (FC) and size (FS), uterine area (UA) and endometrial thickness (Endo) were determined by ultrasonography. Results: The ovarian morphology showed a significant decrease in group II; the OV transabdominally was 14.26± 2.42 vs 10.56±1.0 (0.001) and transvaginally 14.93±2.55 vs 11.75±1.06 (0.001). The FC was 14.00±1.60 vs 12.3±0.78 (0.023) and FS was 8.23±8.9vs 3.29±6.9 (0.001). The uterine morphology however showed a significant increase in group II. The UA was 88.79±5.83 vs 119.71±22.83 (0.001) and endo was 0.56±0.10 vs 0.67±0.12 (0.001) Conclusion: The ovarian morphology variables which include OV, FC and FS decreases in the older infertile group of women with PCOs but the uterine morphology variables showed an increase in area with thickening of endometrium in the older group.